Faith, Ritual, and Social Boundaries: An Analysis of Religious Behavior in the An-Nadzir Community of South Sulawesi - Andi Dody May Putra Agustang; Muhammad Nur; Indriani (BELIEF: Sociology of Religion Journal, 2025)
This study aims to analyze the religious behavior of the An-Nadzir community in Romang Lompoa Village, Bontomarannu District, Gowa Regency, South Sulawesi. The focus of the research is directed at the dimensions of religious behavior, influencing factors, and its social implications in the context of the local community. The research method uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation of five key informants consisting of religious figures, community leaders, and ordinary members. Data analysis was conducted using thematic methods, complemented by source and method triangulation techniques to maintain validity. The results show that the religious behavior of the An-Nadzir community includes a cognitive dimension in the form of belief in the importance of upholding Allah's law and the sunnah of the Prophet; an emotional dimension that brings peace and spiritual experience to members; and a behavioral dimension in the form of the Latiful Akbar dhikr ritual, distinctive prayer procedures, and outward symbols such as turbans, veils, and blond hair. The community structure is organized through hierarchical leadership centered on an amir. Interactions with the outside community are relatively harmonious through mutual cooperation and economic engagement, although the community often faces stigma and criticism. The study's conclusions confirm that the An-Nadzir community is able to survive as a minority religious group through internal solidarity, social openness, and resilience in maintaining its religious identity. These findings contribute to the literature on minority religiosity in Indonesia and offer practical implications for strengthening pluralism and social tolerance.